Keabsahan Alat Bukti Digital Berbasis Internet of Things dalam Hukum Acara Pidana Menurut Undang-Undang Nomor 20 Tahun 2025 - Moh. Mujibur Rohman; Andes Robensyah; Ludfi; Jamaludin (Jurnal Hukum Siber dan Regulasi Teknologi, 2026)
The utilization of Internet of Things (IoT) devices in everyday social life has generated digital data that is increasingly used as evidence in criminal cases. This development raises legal issues concerning the status and validity of IoT-based digital evidence within the Indonesian criminal procedure system following the enactment of Law Number 20 of 2025 on the Criminal Procedure Code. This study focuses on analyzing the legal validity of IoT-based digital evidence and its implications for the protection of suspects’ rights in the criminal evidentiary process. The research employs a normative juridical method by examining statutory provisions, principles of criminal evidence law, and relevant legal doctrines. The findings indicate that IoT-based digital evidence is recognized as legally valid provided that it is obtained lawfully, meets the requirements of data authenticity and integrity, and is supported by digital forensic examination and expert testimony. However, the use of such evidence also poses risks to the right to privacy and the principle of due process of law if it is not accompanied by clear and proportionate procedures. Therefore, strengthening technical and procedural regulations, as well as enhancing the capacity of law enforcement authorities, is necessary to ensure that the use of IoT evidence operates fairly and in balance within the criminal justice system.